Effects of irrigation type and fertilizer application rate on growth, yield, and water and fertilizer use efficiency of silage corn in the North China Plain - Liu, Yuchun; Wang, Ning; Jiang, Changsong; Wang, Yao (PeerJ, 2024)
Background There is an urgent need to save water and decrease fertilizer application rates in agricultural areas of the North China Plain (NCP) and similar regions. Methods Field experiments were conducted in 2017 and 2018 in the NCP to investigate the effects of border and furrow irrigation under different fertilizer application rates on the growth, yield, and water and fertilizer use efficiencies of silage corn. The experiment applied two irrigation methods, i.e., border and furrow irrigation, each with four compound fertilizer application rates: 750, 600, 450, and 300 kg/ha. Results While the two experiment years were normal hydrological years, variation in precipitation resulted in no irrigation being applied in 2017 and 70 mm of irrigation being applied after sowing in 2018. Plants appeared to grow slightly taller and thicker with larger leaf areas, but with a 9.7% lower fresh weight yield in 2017 relative to 2018. The actual evapotranspiration (ETa) in 2017 was 37.22 mm more than that in 2018, and the higher fresh weight yield and lower ETa caused higher water use efficiency (WUE) in 2018, which was 32% higher than that in 2017. Furrow irrigation promoted growth compared with border irrigation under the same irrigation amount, but without significant effects on fresh weight yield, ETa, or WUE of silage corn. The fertilizer application amount had a significant effect on fresh weight yield and the partial fertilizer productivity of N, P and K of silage corn, but did not affect ETa or WUE of silage corn. Additionally, the fertilizer rate of 600 kg/ha induced slightly higher growth indexes and fresh weight yields compared with the fertilizer rates of 750, 450, and 300 kg/ha. Discussion In the NCP, lower irrigation amounts at the crop development period of silage corn appeared to promote higher yield, WUE, and fertilizer use efficiency, under the condition that there was sufficient water to ensure the emergence of seedlings. The current fertilizer application model, compound fertilizer applied with a seeder at planting, does not match the fertilizer needs of silage corn, and more efficient water and fertilizer application techniques should thus be adopted.
Keywords: Irrigation type; Fertilizer rate; Silage corn; Water and fertilizer use efficiency; North China Plain